Microbial pathogenesis revealed by intravital microscopy: pros, cons and cautions - Stolp-Rastätter, Bettina; Melican, Keira (FEBS letters, 2016)
Intravital multiphoton imaging allows visualization of infections and pathogenic mechanisms within intact organs in their physiological context. Today, most organs of mice and rats are applicable to in vivo or ex vivo imaging, opening completely new avenues for many researchers. Advances in fluorescent labeling of pathogens and infected cells, as well as improved small animal models for human pathogens, led to the increased application of in vivo imaging in infectious diseases research in recent years. Here, we review the latest literature on intravital or ex vivo imaging of viral and bacterial infections and critically discuss requirements, benefits and drawbacks of applied animal models, labeling strategies, and imaged organs.
Gesehen am 12.02.2019